Impact of dust loading on ozone, winds and heating rates in the atmosphere of mars: Seasonal variability, climatology and SPICAM observations. (March 2022) - Haider, S.A.; Siddhi, Y.S.; Masoom, J.; Sheel, Varun; Kuroda, T.
Abstract: We have used SPICAM-UV nadir observations for four Martian Years (MY27-MY30) to study the seasonal variability of column abundances of ozone and dust opacity at low latitudes (10°-30°), mid-latitudes (30°-50°) and high latitudes (50°-70°) in both hemispheres. The observed column abundances of ozone are compared with the Mars Climate Database (MCD, version 5.3) between MY27 and MY30 at these latitudes. In these observations year-to-year seasonal variability of column ozone were nearly the same except the enhancement in MY28 in the latitude range ∼10-30°S and Ls∼270°-310° when a global dust storm occurred. We have also calculated vertical profiles of O3 heating rates from the MCD model in presence of a dust storm at different latitudes and solar longitudes. At low and mid-latitudes, the ozone heating rates increase until Ls ∼47.5°. Afterwards, they decrease until Ls∼ 127.5° and then they reached a minimum value between Ls∼ 167.5° and 327.5°. In the presence of a dust storm, ozone heating rates increase by a factor of 2.5–3 up to 10 ​km at Ls∼280°. MCD results are also used to study the seasonal variability of zonal, meridional and vertical winds in the tropical atmosphere of Mars during MY28 and MY29. It is found that the density of ozone, wind speeds and ozone heating rates are severely affected by the global dust storm up to 10 ​km at latitude ∼25°S for Ls ∼270°-310°. Highlights: Seasonal variability of column abundances of SPICAM observed by ozone and dust opacity at low, mid and high latitude. Impact of Dust loading on ozone density, winds and heating rates in Mars' atmosphere. Seasonal and latitudinal variability of ozone heating rate.